2021
DOI: 10.1186/s12870-021-02847-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and genome-wide association study reveal long noncoding RNAs responding to nitrogen deficiency in maize

Abstract: Background Long noncoding RNAs (lncRNAs) play important roles in essential biological processes. However, our understanding of lncRNAs as competing endogenous RNAs (ceRNAs) and their responses to nitrogen stress is still limited. Results Here, we surveyed the lncRNAs and miRNAs in maize inbred line P178 leaves and roots at the seedling stage under high-nitrogen (HN) and low-nitrogen (LN) conditions using lncRNA-Seq and small RNA-Seq. A total of 894… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 65 publications
(76 reference statements)
0
13
0
Order By: Relevance
“…A large number of LN‐responsive candidate genes were identified using a GWAS, which combined high‐density SNPs (56,110 SNPs) from an association mapping panel with 17 variable seedling phenotypes under contrasting N concentrations (Ma et al . 2021). To investigate the regulatory roles of circRNAs–parent genes in maize seedlings under LN stress, we combined the candidate genes screened with LN‐responsive GWAS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of LN‐responsive candidate genes were identified using a GWAS, which combined high‐density SNPs (56,110 SNPs) from an association mapping panel with 17 variable seedling phenotypes under contrasting N concentrations (Ma et al . 2021). To investigate the regulatory roles of circRNAs–parent genes in maize seedlings under LN stress, we combined the candidate genes screened with LN‐responsive GWAS.…”
Section: Resultsmentioning
confidence: 99%
“…The transcriptome and small RNA data were collected from our previous study (Ma et al . 2021), including 24 samples from HN and LN conditions. The dataset can be downloaded from NCBI under the accession numbers PRJNA661965 and PRJNA662035.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have demonstrated the changes in the expression level of different miRNA families in N limitation conditions in various plant species such as Arabidopsis [ 51 , 52 ], maize [ 53 , 54 ], sorghum [ 55 ], rice [ 32 ], and soybean [ 33 ]. The altered expression pattern of these miRNAs has been shown to play crucial roles in plant adaptive responses to N limitation via the mediation of the expression of their target genes involved in N uptake and remobilization [ 56 ].…”
Section: Biological Functions Of Micrornas In N Metabolismmentioning
confidence: 99%
“…There were 1229 differently expressed heat-responsive lncRNAs in Chinese cabbage [ 18 ]. In the maize root, a total of 40 distinct expressed lncRNAs implicated in nitrogen uptake were discovered [ 19 ]. The competitive endogenous (ce) RNA hypothesis has gained traction as a putative stress-resistance regulation mechanism in plants.…”
Section: Introductionmentioning
confidence: 99%